Adaptive steganography algorithm in digital image based on Arnold transform - Qi LI; Xin LIAO; Guo-qing QU; Guo-yong CHEN; Jiao DU (Tongxin xuebao)
Previous adaptive steganography algorithms were based on ordinal and full-embedding method.However,these algorithms might cause the concealment of secret information not good enough.Therefore,a random and non-fully embedding method was proposed to improve the concealment.The image system parameters could be obtained,so that the image full capacity was exactly greater than the length of information for non-full embedding.Moreover,these parameters made steganography more flexibility by reducing the modifications of image.Then,secret information embedding sequence was scrambled based on Arnold transform for the purpose that the steganalyst cannot detect out information orderly.Therefore,the secret information can be more concealed,which can improve the security of the algorithms.Experimental results show that the algorithm not only improves the concealment of steganography but also reduces stego distortion,and random non-full embedding operating can be applied to many other similar algorithms.